A review and evaluation of marital and family therapies for affective disorders. - Prince, Stacey E.; Jacobson, Neil S. (Journal of Marital & Family Therapy, 1995)
Part of a special issue on the effectiveness of marital and family therapy. The writers assess the present status of marital and family therapies for affective illness. A number of lines of research bearing on the relationship between family processes and affective illness are examined. A review of the available treatment outcome data assessing the efficacy of marital and family interventions is provided, with specific attention paid to predictors of treatment success and cost efficacy issues. Finally, several priorities for further research are proposed.